220 MHz Proton Nuclear Magnetic Resonance Study of the Interaction between Chicken M(4) Lactate Dehydrogenase and Reduced Diphosphopyridine Nucleotide - Sarma, Ramaswamy H. (1970)
220 MHz proton nuclear magnetic resonance investigations of reduced pyridine coenzymes and coenzyme fragments, both in the presence and absence of M(4) lactate dehydrogenase, show the following: (1) That the energy barrier between a folded and open conformation of the reduced pyridine coenzyme (in aqueous solutions) is insignificant because an unfavorable enthalpy change of 5 kcal is compensated for by a favorable entropy change of 19 entropy units. (2) The coenzyme, however, appears to maintain its intramolecularly folded conformation on contact with the enzyme. The binding of the coenzyme results in the immobilization of the adenine and pyridine moieties and there is no longer any gain in the conformational entropy as a result of unfolding as in aqueous solutions. (3) The purine moiety of the coenzyme facilitates the binding of the pyridine ring and indicates how high frequency nuclear magnetic resonance can be utilized to study binding of small molecules to enzymes.